A Positive Change Trinity: Lean, Servant Leadership, and Maine - Maxwell, William; Gibson, Joyce (Maine Policy Review, 2018)
This article is a call to action for Maine’s entrepreneurial servant leaders. We believe you can be a prime catalyst for positive change in Lean/Continuous Improvement initiatives across Maine. We are proposing that Maine’s servant leaders leverage the tool of Lean/Continuous Improvement to ignite a positive shift in organizational cultures. Our positive change trinity encompasses (1) Lean/Continuous Improvement as the process map of how to achieve new, sustainable growth; (2) servant leadership as the synergist that humanizes this growth in the territory of Maine workers’ lived experience; and (3) Maine’s forward-thinking businesses as the real-world hosts for this growth.
Keywords: Lean/Continuous Improvement; business leadership; servant leadership; Maine